Implementasi Pendidikan Karakter Berbasis Multikultural Dalam Pembentukan Kepribadian Unggul Siswa Di MAN 3 Jombang - Atho' Alaul Huda, Saihul; Latifatul Aini, Nurul (Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to find out how the implementation of multicultural-based character education in the formation of students' superior personalities at MAN 3 Jombang, using the observation method, data analysis techniques using surveys and interviews. 3 Jombang, one of which is in BK learning, that is, most students can comply with all madrasa rules and regulations and also in this counseling guidance students can also understand their environment and solve problems and can socialize well according to the rules that apply at school.